Відповідь:
Пояснення:
1) a⁴x + a⁴ + a³x + a³ = a³( ax + a + x + 1 ) = a³ [ a( x + 1 ) + ( x + 1 ) ] =
= a³( a + 1 )( x + 1 ) ;
2) p³a²+ ра² – Зар³ - Зар = pa²( p + 1 ) - 3ap( p + 1 ) =
= ( p + 1 )( pa²- 3ap ) = ap( p + 1 )( a - 3 ) .
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Відповідь:
Пояснення:
1) a⁴x + a⁴ + a³x + a³ = a³( ax + a + x + 1 ) = a³ [ a( x + 1 ) + ( x + 1 ) ] =
= a³( a + 1 )( x + 1 ) ;
2) p³a²+ ра² – Зар³ - Зар = pa²( p + 1 ) - 3ap( p + 1 ) =
= ( p + 1 )( pa²- 3ap ) = ap( p + 1 )( a - 3 ) .